There is another: H3K27me3-mediated genomic imprinting. Issue 1 (January 2022) - Raas, Maximilian W.D.; Zijlmans, Dick W.; Vermeulen, Michiel; Marks, Hendrik
Abstract : DNA methylation has long been considered the primary epigenetic mediator of genomic imprinting in mammals. Recent epigenetic profiling during early mouse development revealed the presence of domains of trimethylation of lysine 27 on histone H3 (H3K27me3) and chromatin compaction specifically at the maternally derived allele, independent of DNA methylation. Within these domains, genes are exclusively expressed from the paternally derived allele. This novel mechanism of noncanonical imprinting plays a key role in the development of mouse extraembryonic tissues and in the regulation of imprinted X-chromosome inactivation, highlighting the importance of parentally inherited epigenetic histone modifications. Here, we discuss the mechanisms underlying H3K27me3-mediated noncanonical imprinting in perspective of the dynamic chromatin landscape during early mouse development and explore evolutionary origins of noncanonical imprinting. Highlights: Trimethylation of lysine 27 of histone H3 (H3K27me3) is a novel DNA-methylation-independent mediator of genomic imprinting in mice. H3K27me3-mediated noncanonical imprinting underlies imprinted paternal X chromosome inactivation during preimplantation of mouse development and is essential for proper development of extraembryonic tissues. Lack of H3K27me3-mediated noncanonical imprinting in somatic cells impedes post-implantation development of embryos derived from somatic cell nuclear transfer (SCNT). Noncanonical imprinting in mouse embryos is likely associated with the relative slow dynamics with which H3K27me3 equalizes between both parental alleles after fertilization. H3K27me3-mediated imprinting as observed in mice and plants seems to have evolved convergently.